Deteksi Rhodamin B pada Perona Pipi Murah di Kota Bandar Lampung - Rina Budi Satiyarti; Noviana Anggaraini; Iip Sugiharta (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2021)
Rhodamin B dye is dyes belongs to the cationic dye class which is included as a hazardous material in medicine, food, and cosmetics. Rhodamin B effect could cause growth retardation, liver damage, and defense of the cell's full immune response. This day, Rhodamin B found in food and cosmetics products. This research was conducted to detect and detremine the levels of Rhodamin B in blusher which is marketed in the largest market, namely central market in Bandar Lampung city. Blusher samples were taken from three brands. Rhodamin B dye was identified by TLC method with ethyl acetate-methanol-amonia (75:30:15), detected in UV light 254 nm in wavelength. Concentration of Rhodamin B were calculated by UV-Vis spectrophotometry. The results showed that from 3 samples, 2 samples were contained Rhodamin B, detected from Rf 0.99 cm (for sample 2) and 0.95 cm (for sample 3) with a 0.97 cm standard. Rhodamin B concentration was 0.2299 mg/g for sample 2, while it was not detected in sample 3. Keywords: blush on, Rhodamin B, UV-Vis spectrophotometry